Effect of Inclined MHD Peristaltic Transport for non-Newtonian model in a Non-Uniform Channel Through Porous Medium As: HTF - Ridha, Safa Riyadh; Solagh, Hussam Numan (Iraqi Journal of Science, 2025)
The current work aims to study the effect of an inclined magnetohydro dynamics peristaltic transport of a non-Newtonian hyperbolic tangent fluid in a non-uniform channel via porous medium. The nonlinear governing equations regarding hyperbolic tangent fluid have been studied and solved analytically with the use of a regular perturbation approach under considerations of a long wavelength as well as low Reynolds number. All computational results are also discussed graphically using the MATHEMATICA program. The mathematical expressions for axial velocity and stream functions have been derived analytically. Different physical parameters have been shown graphically and discussed it’s effect. It is established that increasing the Hartmann number and the parameter of porosity will increase the velocity and the quantity of boluses. While the size of boluses decreases by increasing the magnetic field inclination angle. Moreover, Some mathematical and engineering aspects of non-Newtonian fluids are investigated in the current analysis.